2007
DOI: 10.1007/s11483-007-9027-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Processing and Storage Parameters on the Oxidative Deterioration of Oil-in-Water Emulsions

Abstract: The effect of storage temperature, pH, and homogenization pressure on the oxidative deterioration of Tween 20 and sodium caseinate sunflower oil-in-water emulsions was studied by monitoring conjugated dienes (CD), lipid hydroperoxides (LH), and thiobarbituric acid reactive substances (TBARs). CD increased linearly with storage time, and the rate constant was temperature dependent according to the Arrhenius equation with an activation energy equal to 37.5 kJ mol −1 . The increase in LH and TBARs with temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 31 publications
5
51
0
Order By: Relevance
“…Conversely, the rate constant for the last half of the methyl α-linolenate autoxidation was smaller for emulsions with larger oil droplet sizes. Roozen et al 12 and Dimakou et al 14 have reported that the autoxidation of linoleic acid and sunflower oil, respectively, containing linoleoyl residues did not depend on oil droplet size in O/W emulsion systems, findings similar to our results. Therefore, in the case of n-6 polyunsaturated fatty acids (2) and (4), respectively.…”
Section: Au Tox I D a T I O N O F M E T Hy L L I N O L E A Te A N D Msupporting
confidence: 92%
“…Conversely, the rate constant for the last half of the methyl α-linolenate autoxidation was smaller for emulsions with larger oil droplet sizes. Roozen et al 12 and Dimakou et al 14 have reported that the autoxidation of linoleic acid and sunflower oil, respectively, containing linoleoyl residues did not depend on oil droplet size in O/W emulsion systems, findings similar to our results. Therefore, in the case of n-6 polyunsaturated fatty acids (2) and (4), respectively.…”
Section: Au Tox I D a T I O N O F M E T Hy L L I N O L E A Te A N D Msupporting
confidence: 92%
“…As such, surface-active LOOHs could concentrate at the oil-water interfaces of bulk oils, oil-in-water emulsions, or membrane systems. Indeed, several authors have reported the presence of LOOH at the emulsion droplet surface (Dimakou et al 2007;Mancuso et al 2000;Mei et al 1998a,b;Nuchi et al 2002;Yoshida & Niki 1992). In membrane systems, LOOHs float on the LDL surface (Ingold et al 1993).…”
Section: Self-assembly Of Lipid Hydroperoxides As a Trigger Of The Prmentioning
confidence: 99%
“…8 Briefly, 700 μL of distilled water and 2 mL of TBA solution (prepared with 15 g trichloroacetic acid, 0.375 g TBA, 1.76 mL 12 M HCl and 82.9 mL H2O) were added to 300 μL of the sample solution, and vortex-mixed for 15 s. The mixture was heated in a boiling water bath for 15 min and then cooled at room temperature for 10 min. The sample was centrifuged for 15 min at 650g and the absorbance of the supernatant at 532 nm was measured.…”
Section: Tba Assay Proceduresmentioning
confidence: 99%
“…The incubation temperature of 60 C was adopted according to the literature. 5,8 The emulsions were prepared with 0.2% w/v oil and 0.02% w/v Tween 20. As shown in Fig.…”
Section: Effect Of the O/w Emulsion Conditions On The CL Intensitymentioning
confidence: 99%
See 1 more Smart Citation